PEMAKNAAN UMAT BUDDHA VIHARA LALITAVISTARA TERHADAP ALAM SUKHAVATI - Nyoto, Nyoto (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2023)
Abstract Lalitavistara Temple is a Mahayana temple of Maszab Sukhavati, the Buddhists of the temple really glorify Amitaba Buddha and some call it Amitayus Buddha. Devotees who praise Amitaba Buddha have the belief that after death they will be reborn in Sukhavati. In the Sukhavati Maszab teachings by reciting Amitaba Buddha's name, whatever you want will be achieved. Sukhavati is a plane of existence outside the cycle of the 31 planes of existence known to Buddhists. This realm is far from the human realm inhabited by the followers of Amitaba Buddha. Beings in Sukhavati are constantly training themselves and practicing Amitaba Buddha's teachings to achieve eternal happiness (Nirvana) This research is a descriptive qualitative research. So that the data obtained are satisfactory, the authors carry out observations, interviews, and documentation so that the data obtained are accurate. The researcher also sought information from other secondary sources such as articles and books related to Sukhavati. The results of research conducted at Lalitavistara Temple in Jakarta on Buddhist understanding of the Sukhavati realm are that some people think that the realm of Sukhavati is the same as the heaven realm inhabited by the gods, there are some who say that Sukhavati is a realm inhabited by Bodhisattvas who glorify Amitaba Buddha. , and some say that Sukhavati is a heaven in the west. Next the devotees explain that to attain Sukhavati is by doing good, developing prajna, and praising Amitaba Buddha. Keywords: Sukhavati, Mahayana School, Buddha Dharma.